Multidisciplinary optimisation of aero-engines using genetic algorithms and preliminary design tools - Whellens, Matthew W. (Cranfield University, 2003)
This study investigates a novel methodology for the preliminary design of aeroengines. This involves the modelling of the disciplines that affect the engine's requirements and constraints, their implementation in software format and their coupling into a single unit. Subsequently, this unit is interfaced with an optimiser software. The resulting multidisciplinary optimisation (MDO) tool allows the automation of the traditional, human-based preliminary design process. The investigation of the above-mentioned novel methodology is carried out through the development of a "pilot" MDO tool and its subsequent utilisation in three case studies, characterised by different optimisation scenarios. The selection of each case study is motivated by current research questions, such as aviation's contribution to climate change or the attractiveness of specific novel propulsion concepts. The outcome of the pilot MDO study is considered successful and has been well received by several academic and industrial aero-engine organisations. The choice of the disciplines and of their modelling fidelity allowed a realistic representation of the main disciplinary interactions and tradeoffs that characterise the important phase of preliminary design. The computational effort involved in the solution of the optimisation studies was found to be acceptable, and no major reprogramming was required when different optimisation scenarios were considered. The case studies were investigated with an ease and comprehensiveness that would not have been achievable through a human-based parametric analysis. The positive experience with the pilot MDO tool suggests that an automated methodology for the preliminary design of aero-engines is feasible, applicable and valuable. Its adoption can provide substantial advantages over the traditional human-based approach, such as a reduction in human effort, costs and risk. From this perspective, the pilot study constitutes a first step towards the development of a full-scale MDO tooL usable by aero-engine manufacturers. In the near future, issues like climate change could drive significant modifications in airframe and engine design. A preliminary design MDO tool is therefore timely, and has the potential of making a significant contribution.